2014
DOI: 10.5713/ajas.2013.13437
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Efficiency and Meat Oxidative Stability and Microbiological Quality of New Zealand White Rabbits Subjected to Halal Slaughter without Stunning and Gas Stun-killing

Abstract: A study was conducted to compare the effect of halal slaughter without stunning and gas stun killing followed by bleeding on residual blood content and storage stability of rabbit meat. Eighty male New Zealand white rabbits were divided into two groups of 40 animals each and subjected to either halal slaughter without stunning (HS) or gas stun-kill (GK). The volume of blood lost during exsanguination was measured. Residual blood was further quantified by determination of haemoglobin content in Longissimus lumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 44 publications
10
58
0
Order By: Relevance
“…However, no group (HS or AS) had TBARS value that reached detectable concentration for humans as established by Insausti et al (2001). The similarity in lipid oxidation observed in the present study corroborates the report of Nakyinsige et al (2014) in rabbits, which showed that slaughter…”
Section: Meat Lipid Oxidationsupporting
confidence: 95%
See 3 more Smart Citations
“…However, no group (HS or AS) had TBARS value that reached detectable concentration for humans as established by Insausti et al (2001). The similarity in lipid oxidation observed in the present study corroborates the report of Nakyinsige et al (2014) in rabbits, which showed that slaughter…”
Section: Meat Lipid Oxidationsupporting
confidence: 95%
“…For instance, glucose which is the substrate preferentially used by many microorganisms such as Pseudomonas (Warriss, 2000) when growing in meat is readily available in blood. Nakyinsige et al (2014) observed that lower amount of residual blood in the carcass of rabbits subjected to halal slaughter caused lower bacteria count. In chicken, Ali, Abdalla, and Mahgoub (2011) also reported that higher blood loss in halal slaughter was associated with lower bacteria count in minced meat at 48 h postmortem.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 2 more Smart Citations
“…After subtracting the OD of blank (standard 4) from all standard and sample values, a standard curve was obtained by plotting the ∆OD 535 against standard concentrations. TBARS (µM MDA equivalent) concentration of the samples was calculated according to the equation: [TBARS] = [(R sample -R blank ) ÷ Slope (µM -1 )] × n(Nakyinsige et al, 2014).…”
mentioning
confidence: 99%